Postsocialism - Martin, D (Open Knowledge Press, 2021)
The collapse of the socialist societies in Eastern Europe and the Soviet Union drastically changed the lives of millions of people and offered a new and exciting field of research possibilities. ‘Postsocialism’ emerged as an interim term to describe the lives of people who had formerly lived under socialism. Some scholars of postsocialism assumed a quick transition for these societies to neoliberal forms of government and economy. However, postsocialism did not simply follow on from socialism, and socialism did not simply go away. Key postsocialist works indicate that postsocialist forms of being were established well before socialism’s political demise. Similarly, some of socialism’s material forms and social norms continued and have proved to have a resilient afterlife. The confident assertion that socialism’s fall signals the ‘end of history’ has been challenged by philosophy and by events. This entry surveys the roots of postsocialism as an anthropological concept, and interrogates the concerns as to its long-term viability as an organising category for the study of societies becoming more diverse as they distance themselves from their socialist pasts. However, the former socialist societies have provided a range of rich anthropological research opportunities for scholars and continue to afford unique insights into key areas of ethnographic and theoretical interest. One possible future for what is still called postsocialism might be its amalgamation with postcolonialism, as a new hybrid area of scholarship, focused upon societies whose histories and ideologies challenge the hegemonic narrative of neoliberal modernity.